THE GEOLOGICAL WATER CYCLE AND THE EVOLUTION OF MARINE δ18O VALUES - Wallmann K. (My University, 2001)
The turnover of water and 18O in the outer terrestrial sphere is investigated considering mantle degassing, subduction zone processes, hydrothermal circulation at spreading centers, seafloor alteration, and continental weathering processes. Mass balances indicate that the ocean currently loses water to the mantle because the water emission by mantle degassing proceeds at a significantly slower rate than the subduction of water structurally bound in the down-going slab. The current input of 18O into the ocean through hydrothermal circulation and water emissions at arc volcanoes surpasses the fixation of 18O via low-temperature water/rock interactions at the seafloor and on continents, inducing an increase in marine δ18O values. Results of a box model simulating the Phanerozoic water and 18O cycles suggest that the mass of seawater decreased significantly causing a continuous drop in global sea-level by several hundred meters over the Phanerozoic. Model results and mass balances also allow for an enhanced estimate of current water fluxes in subduction zones consistent with the secular changes in sea-level and marine δ18O observed in the geological record. Moreover, the model generates a secular trend for seawater δ18O-produced by the surplus of 18O inputs and through internal feed-backs associated with isotopic exchange reactions at the seafloor-comparable to that observed in Phanerozoic carbonates. This coincidence suggests that the marine carbonates record a continuous change in isotopic composition of seawater with superimposed temperature-related fluctuations. A continuous record of near-surface temperatures was calculated using the model curve for seawater δ18O and the corresponding carbonate data. This new climate record indicates three icehouse-greenhouse cycles with a duration of 127 My between the Cambrian and the Triassic followed by an additional cycle with extended periodicity spanning the Jurassic to Cenozoic. Simulations of the Precambrian water and 18O cycles imply that the strong 18O depletion in seawater during the early Cambrian (δ18O around -8 %%) was caused by enhanced weathering, diminished hydrothermal activity and extreme glaciations during the preceding late Neo- proterozoic.
Keywords: Jurassic; Cenozoic; Cambrian; Precambrian; Triassic; Proterozoic; Кайнозой; Paleozoic::Cambrian; Precambrian::Proterozoic; Precambrian; Mesozoic::Triassic; Mesozoic::Jurassic; Cenozoic; Мезозой::Триасовая; Мезозой::Юрская; Палеозой::Кембрийская; Докембрий::Протерозой; Докембрий